2017
DOI: 10.1038/ncomms14441
|View full text |Cite
|
Sign up to set email alerts
|

Tunable thermal expansion in framework materials through redox intercalation

Abstract: Thermal expansion properties of solids are of fundamental interest and control of thermal expansion is important for practical applications but can be difficult to achieve. Many framework-type materials show negative thermal expansion when internal cages are empty but positive thermal expansion when additional atoms or molecules fill internal voids present. Here we show that redox intercalation offers an effective method to control thermal expansion from positive to zero to negative by insertion of Li ions int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 56 publications
4
88
1
Order By: Relevance
“…[40] Thermal expansion changes substantially after the insertion of H 2 Oi nto ZnPt(CN) 6 . [44] Herein, we demonstrate that the thermal expansion of YFe(CN) 6 -based Prussian blue analogues can be switched substantially from negative to positive by introduction of guest molecules (H 2 O) and ions (K + )tothe void spaces of its framework structure.C rystal structures and thermal expansions were determined by high-resolution synchrotron X-ray diffraction (SXRD), neutron powder diffraction (NPD), and from the temperature dependence of XRD.T he role of the guest ions and molecules upon switching of the thermal expansion is explained by the solid state structure and the characteristics of the lattice dynamics.T he present approach permits tailoring of thermal expansion and may be extended to many other NTE framework materials. [42] Similar interesting phenomena were also observed in MOFs.…”
mentioning
confidence: 86%
“…[40] Thermal expansion changes substantially after the insertion of H 2 Oi nto ZnPt(CN) 6 . [44] Herein, we demonstrate that the thermal expansion of YFe(CN) 6 -based Prussian blue analogues can be switched substantially from negative to positive by introduction of guest molecules (H 2 O) and ions (K + )tothe void spaces of its framework structure.C rystal structures and thermal expansions were determined by high-resolution synchrotron X-ray diffraction (SXRD), neutron powder diffraction (NPD), and from the temperature dependence of XRD.T he role of the guest ions and molecules upon switching of the thermal expansion is explained by the solid state structure and the characteristics of the lattice dynamics.T he present approach permits tailoring of thermal expansion and may be extended to many other NTE framework materials. [42] Similar interesting phenomena were also observed in MOFs.…”
mentioning
confidence: 86%
“…98 It has also been found that NTE in ScF 3 can be essentially turned off by doping with a small amount of Fe and intercalating an equal amount of Li into the vacant A-sites. 99 The inclusion of Li ions limits the transverse vibrations of the fluoride ions, much the same way that guest molecules can dampen NTE in other porous NTE materials. [100][101][102][103][104] Redox active MF 3 materials that have been examined as intercalation materials for batteries include those where M = Ti, V, Mn, Co, and Fe.…”
Section: Inorganicsmentioning
confidence: 99%
“…In addition to cyanides (Chapman et al, 2006; Phillips et al, 2008), the fluoride group (Greve et al, 2010; Attfield, 2011; Chatterji et al, 2011; Chen et al, 2017), such as ScF 3 and ZnF 2 , has attracted attention recently. Particularly, Cd(CN) 2 · x CCl 4 shows large NTE of α L = −34 × 10 −6 K −1 and Δ V / V = 2.1% at T = 175–375 K (Phillips et al, 2008).…”
Section: Positive and Negative Thermal Expansionmentioning
confidence: 99%